ANALISIS FAKTOR-FAKTOR YANG MEMPENGARUHI KEPUTUSAN INVESTASI PADA GENERASI MILENIAL DI INDONESIA - Hasan Husaini (Jurnal Penelitian Ekonomi dan Manajemen (JPEM), 2026)
Investment decisions among millennials have become an increasingly important phenomenon in the era of technological advancement and digitalization of the financial sector. This study aims to analyze the factors influencing investment decisions among millennials in Indonesia. The research method used is a qualitative approach through a literature review of relevant scientific journals, books, and official publications. The findings indicate that millennials’ investment decisions are influenced by several key factors, including financial literacy, income, digital technology development, social media influence, risk level, and lifestyle. The ease of access to digital investment platforms has also increased investment interest among millennials. However, challenges such as low investment understanding, consumptive behavior, and trend-driven decision making still exist. Therefore, improving financial education and strengthening investment literacy are essential in creating more rational and sustainable investment decisions